Predictors of Postoperative Complications Following Transurethral Resection of the Prostate: A Prospective Cohort Study - Naveed Ahmad, Syed Hamzah Shirazi, Numan Alam, Aziz Ul Wahab, Riaz Ali Khan (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Transurethral resection of the prostate (TURP) remains a standard surgical treatment for benign prostatic hyperplasia, but postoperative complications still contribute to morbidity and prolonged recovery. Objective: To determine the incidence and predictors of postoperative complications following TURP. Methodology: This prospective cohort study was conducted at Mansehra medical complex, Mansehra , KP ,Pakistan from June 2022 to June 2023. A total of 295 patients undergoing TURP were enrolled and followed for 30 days postoperatively. Results: The mean age was 68.4 ± 8.7 years and mean BMI was 27.1 ± 4.2 kg/m². Hypertension was present in 184 (62.4%), diabetes in 109 (36.9%), and ASA class III–IV in 114 (38.6%) patients. Postoperative complications occurred in 67 (22.7%) patients. The commonest complications were urinary tract infection 24 (8.1%), clot retention 21 (7.1%), and bleeding requiring transfusion 16 (5.4%). Operative time >60 minutes was the strongest predictor of complications (aOR 2.67, 95% CI 1.49–4.79, p=0.001), followed by ASA class III–IV (aOR 2.31, p=0.005), prostate volume >80 mL (aOR 1.94, p=0.026), age ≥75 years (aOR 1.89, p=0.036), and diabetes mellitus (aOR 1.76, p=0.047). Conclusion: It is concluded that postoperative complications following TURP were common but mostly mild to moderate. Advanced age, diabetes mellitus, higher ASA class, larger prostate volume, and prolonged operative time were significant predictors. Keywords: TURP, benign prostatic hyperplasia, postoperative complications, predictors, prostate volume, operative time.